Mixing of Effluent Surface Jets in Channel Confluences - Behzad, Ehsan (Université d'Ottawa / University of Ottawa, 2024)
Urban development near rivers has led to the increased release of municipal and industrial wastewater into water bodies. When a less-dense discharge is introduced into a denser fluid, it gives rise to a positive buoyant jet. Further, a positive buoyant surface jet is formed when discharged near the free surface. This phenomenon is commonly observed in both natural and industrial settings, such as the release of heated cooling water and discharge of treated wastewater into water bodies. This method is the most traditional and economical method for releasing pollutants into rivers or coastal areas. Due to their limited dilution factor, usually ten or below, surface discharges tend to pose greater environmental risks compared to submerged alternatives. The hydrodynamics of a jet in crossflow is inherently complex, especially when the jet is released in areas of the river with complex structures, such as a confluence channel junction. Confluences are characterized by the convergence of two or more flows and distinguished by complex flow structure, hydraulic geometry, and sediment transport. Understanding the mixing phenomenon in such cases is crucial for accurately predicting environmental impacts. This study investigates the surface discharges of jets into confluence waterbodies through both numerical simulations and experimental methods. Experimental studies on buoyant and non-buoyant surface discharges of jets into crossflow were carried out in this research. A new experimental setup was designed and constructed in the Civil Engineering Hydraulics Laboratory at the University of Ottawa to conduct these experiments. laser-induced fluorescence (LIF) experiments were conducted to investigate the combined effects of jet strength and nozzle location on the mixing of a positive or neutral jet issuing into a plane perpendicular to the crossflows. The trajectory and mixing within a channel junction of surface crossflow jets are investigated. The investigations revealed that a jet issued into the main channel mixes more effectively with wider dispersion compared with a jet issued in the tributary. This is due to the shear layer in the main channel, which restricts the jet in tributary to a narrower width, limiting its ability to mix effectively with ambient water. Three-dimensional (3D) Computational Fluid Dynamics (CFD) models were developed to study mixing processes at confluences and the behavior of surface jets discharging into confluence bodies, utilizing various turbulence models. The numerical results for confluence flow were compared against experimental data from existing literature, and subsequent results for mixing of an effluent jet in a confluence flow were compared against experimental work conducted in this study.
Keywords: fluid mechanics; LES; confluence; OPENFOAM; surface positive jet; CFD